Developing with Couchbase Server - Brown, Martin C. (O'Reilly, 2013)
Do you know what to do if your Web application goes viral and usage suddenly explodes? This concise guide introduces you to Couchbase Server, an extremely fast NoSQL database that automatically distributes data across a cluster of commodity servers or virtual machines. You'll learn hands-on how to build a Couchbase cluster without changing your application, and how to expand your database on the fly without interrupting service.--